Improving Students’ Writing Skills through the Application of Synectic Model of Teaching Using Audiovisual Media - Ufi Ruhama; Dewi Ismu Purwaningsih (English Language Teaching Educational Journal, 2018)
Writing might be difficult for some people (Alwasilah, 2007). Some students can speak English fluently and confidently, although since they have difficulties in conveying their ideas in writing. Thus, it needs the effective and efficient model of teaching to improve the teaching learning process. Synectic model of teaching is a model applied to enhance students’ ability to write. This model combines various forms of metaphoric thinking to see old ideas in different ways. In this research, the researcher used audiovisual media to support learning. The purpose of this research is to find out students’ improvement in writing descriptive texts using synectic model of teaching. The sample of the research was 36 students of class IXD in MTsN 2 Pontianak. The research was Classroom Action Research using Kemmis and MC Taggart model with two cycles. The result shows that there is improvement in students writing skill. The mean score of pre-test is 56.01, posttest 1 is 66.5, and posttest 2 is 87.46. It means the application of synectic model of teaching using audiovisual media is able to increase students’ ability in writing descriptive text.